Pre-surgical embolization of intracranial meningioma - Péres, Rafael Jackes (2022)
Introduction: Meningiomas are highly vascularized tumors whose treatment of choice is surgical resection. However, preoperative meningioma embolization was used to facilitate surgical resection, since it can reduce intraoperative blood loss and surgical time. Case report: Female patient, 45 years old, with a history of recurrent headache for six months, who was not given painkillers and has been showing visual deficit with loss of visual field mainly on the left for three months. He underwent brain magnetic resonance and contrast magnetic resonance angiography, which proved to be an extraaxial vascular expansion process in the anterior cranial fossa, being the main hypothesis of lesion of meningothelial lineage (among them or meningioma). Then, he performed a preoperative embolization of the tumor vascularization and, the next day, a neurosur- gery for tumor resection. None of the patient's post-operative courses were without visual impairment, conscious and oriented. Comments: Preoperative embolization can give us an advantage in meningioma surgery. The procedure reduces intraoperative blood loss and operation time, smoothing the tumor's consistency. However, you should pay attention to the possibility of embolic complications and maintain or prepare for emergency craniotomy, especially in patients with large meningiomas.